Metabolic syndrome in colorectal cancer liver metastasis: metabolic reprogramming and microenvironment crosstalk - Ma, Zheng; Wang, Song; Liu, Shanglong; Yang, Wenchang; Hu, Jilin; Lv, Lianghong; Yu, Qian; Lu, Yun (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) ranks as the third most frequently occurring cancer worldwide and the second major contributor to tumor-related mortality, frequently metastasizes to the liver due to its unique vascular and anatomical features, making liver metastasis a critical therapeutic challenge. Metabolic syndrome (MS) is a cluster of conditions characterized by insulin resistance as the core feature, specifically manifesting as obesity, diabetes, hypertension and dyslipidemia, exacerbates CRC progression through multifaceted mechanisms. MS induces mitochondrial dysfunction, oxidative stress, chronic inflammation, and Deoxyribonucleic Acid (DNA) methylation abnormalities, collectively promoting tumor cell proliferation and invasion. In the liver microenvironment, MS-driven metabolic disturbances foster fatty liver formation, alter pH via hyperglycemia, and enhance tumor energy supply. Pro-inflammatory factors and oxidative stress damage hepatocytes and endothelial cells, while immune dysregulation facilitates tumor immune escape. Angiogenic abnormalities further support metastatic growth. Recent studies highlight the strong correlation between metabolic disorders and colorectal cancer liver metastasis (CRLM). Metabolomics has emerged as a pivotal tool for identifying novel biomarkers, offering insights for early diagnosis and prognosis optimization. This article aims to review the metabolic changes in CRLM by exploring metabolic reprogramming, the role of MS in driving CRLM, and the critical importance of metabolomics in CRLM. By providing scientific evidence, this review seeks to identify novel therapeutic targets and develop personalized treatment strategies for patients with CRLM. Furthermore, it aims to further advance the in-depth exploration of CRLM-related mechanisms and promote the rapid development of clinical translation.